THE EFFECTIVENESS OF USING THE DRILL METHOD ON THE LEARNING RESULTS OF CLASS XI STUDENTS EVEN SEMESTER OF SMK - Kartika Ayu Setianingrum; Siti Nur Rohmah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Educational success is influenced by teachers, students, and teaching methods. However, the process of learning mathematics is still teacher-centered, so it has a less significant impact. This result of student's mathematics learning outcomes is still low. This research aimed to know the effectiveness of using the drill method on students the result of learning in XI grade, even semester of State Vocational High School (SMK N) 1 Pajangan Bantul Regency academic year 2017/2018. This type of research is experimental research. The population in this research is class XI students of SMK N 1 Pajangan. Sampling was taken by random sampling technique, class XI Software engineering (RPL) C as an Experiment class, class XI RPL-A as a control class, and class XI RPL B as a trial class. Test instruments used validity test with product-moment correlation formula, reliability with Alpha formula. Data analysis with a hypothesis test, normality test with Chi-Square formula, homogeneity test by Bartlet test. The research results found that the drill method was more effective than the conventional method on students learning outcomes on XI grade, even the SMK N 1 Pajangan Bantul Regency academic year 2017/2018. This can be seen from the second hypothesis's calculation with a significant 5% level and the degree of freedom 44, obtained dan , then .